The Share of Preservation Issues when Planning a Library Building - Varlamoff, Marie-Thérèse (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Primarily and historically a library was a place where books or manuscripts were kept. „ Thékos” means warehouse or storage area in Greek. But nowadays a library is more than a depository. It is also a place where you can read books and access the information they contain. In the case of a new building or of the rehabilitation of an old building it might also serve as a showcase for politicians or decision makers. Hence the necessity to combine preservation issues, accessibility and architecture.